EFEK EKSTRAK ETANOLIK TUMBUHAN SARANG SEMUT (Hydnophytum formicarum) TERHADAP PROLIFERASI SEL LIMFOSIT, VERO DAN T47D DENGAN PENAMBAHAN DOXORUBICIN SECARA IN VITRO - , David Darwis, Prof. Dr. Ediati Sasmito, SE., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Ant plants (Myrmecodia tuberose and M. pendans) extracts have been reported in previous research to have capability in increasing lymphocyte proliferation but being cytotoxic to cancer cell lines. It was expected that the plant extracts can be used as complement to Doxorubicin (Dox), in order to overcome the drugâs immunosuppresant activity. There was no report so far whether another ant plant, i.e. Hydnophytum formicarum also possesses the same activity and whether its ant residue plays a role in the activity. This research aim was to explore the effect of the extracts of this plant and the ant residue on proliferation activity of mouse lymphocyte as well as their cytotoxic effects on Vero and T47D's cell lines in Dox exposure by in vitro technique. Ant plant samples were collected from West Papua. After the hypocotyls were sliced, some parts were dried directly to gain plant with ant residue (B), while other parts were separated from the ant residue to gain plant without ant residue (A) and ant residue (C). Oven dried samples were macerated in 96% ethanol, followed by vacuum evaporation to yield ethanol extract of A,B, and C. Each extract was tested its effect on proliferation activity of Balb/c mice lymphocytes, as well as on T47D and Vero cell lines by MTT assay in various dose (10, 20, 50, 100, and 200 Î¼g/ml) in Dox presence. Hepatitis B vaccine (Engerix BÃ) was used as antigen. Data obtained were analyzed by ANOVA and paired sample T-test. Thin layer chromatography profile of each extract was evaluated to identfy the difference in chemical contents. The result showed that extracts A and B had ability to increase lymphocyte proliferation by increasing dose. Both extracts did not increase Vero cells proliferation in the presence of Dox. However, the addition of extracts A and B increased proliferation of T47D with increasing dose applied. Extract C showed no activity in all assays. There was no chemical content difference observed on extracts A and B. Extract A contained flavonoid, phenolic, aldehyde / ketone and tannin according to TLC detection method with various detection reagents..